Effect of CSR, Firm Size and Investment Decisions on Financial Performance: Consumer Non-Cyclicals Listed on IDX - Bunga Larasyati; Ahmad Rahbani Sulaiman Sirait (JABKO: Jurnal Akuntansi dan Bisnis Kontemporer, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR), firm size, and investment decisions on financial performance, with leverage as a control variable, in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative approach was employed using multiple linear regression on secondary data obtained from annual reports and sustainability reports. The sample was determined through purposive sampling, yielding 30 consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2021–2024 period, with a total of 120 observational data points. The results show that CSR and firm size each have a significant negative effect on financial performance, while investment decisions and leverage show no significant individual effect. Simultaneously, all four variables jointly affect financial performance, explaining 28.7% of the variation in ROA. This study indicates that CSR disclosure and asset scale instead exert negative pressure on profitability, while investment decisions have not been shown to make a significant individual contribution to improving financial performance in the short term.